Literatura infantil e relações étnico-raciais: quais possibilidades para o trabalho junto às crianças? - Camilo, Melissa Lapa (2022)
The present research aims to develop a literature review through research carried out in master's and doctoral programs that involves the field of study of Children's Literature and racial studies in Brazil to answer the research question about what are the possibilities for work next to the children. The methodology used was based on the State of the Art, which allowed an analysis between two theses and fourteen dissertations, available on the BDTD/ibict website. The results showed that despite the obligation of Law 10.639/03, which determines the compulsory teaching of African and Afro-Brazilian history and culture in educational institutions, there is still a myth that children do not understand racial issues, which makes that the school does not deal with this issue in its daily life. In addition, many educators feel unprepared to include the theme in the classroom, as they did not have disciplines at graduation that would help them to reflect on Ethnic-Racial Relations. However, it was concluded that Children's Literature is an act of resistance to the teaching model that has ignored the National Curricular Guidelines for the Education of Ethnic-Racial Relations, as it provides its readers with reflections on respect for differences for an anti-racist society. In addition, it also helps black children to rebuild and regain, in a positive way, their self- image and self-esteem, especially when reading is mediated by the teacher based on the children's own experiences. It was also possible to conclude that only literary works are not capable of changing the social structures already established in society and in education in relation to standards of beauty and cultures considered erudite, legacies of European colonization. For Children's Literature to be a possible way to deal with Ethnic-Racial Relations with children in an education focused on Brazilian decoloniality, there must be a complement between literary works and affirmative actions that credit the experiences of children, such as For example, games, conversation circles and projects aimed at artistic expressions such as music, painting and writing. Thus, in addition to identifying with literary narratives, children also feel more comfortable exposing their feelings and life experiences so that, individually and collectively, they reflect on the way they see themselves and others around them, above all, the behavior of why it is necessary to respect differences, repudiating racism and seeking social equity, through legislative rights and affirmative actions that historically repair the privileges that were denied to members belonging to social minorities. The theoretical framework was based on the new Sociology of Childhood, with William Corsaro and Manuel Sarmento. The references used on Children's Literature were chosen by the authors Nelly Coelho, Regina Zilberman and Ione Jovino. About the epistemologies focused on affirmative actions for an anti-racist Brazilian education, the authors Ângela Figueiredo, Ramón Grosfoguel, Djamila Ribeiro and Chimamanda Adichie were used.